Involvement of free radicals in the cardioprotective effect of defibrotide - (:unkn) unknown (GEORG THIEME VERLAG KG, 1996)
Ischemia followed by reperfusion has deleterious effects on myocardial tissue and a wide range of drugs have been investigated to modulate these changes. Defibrotide (polydeoxyribonucleotides from bovine lung), a drug with antithrombotic and fibrinolytic activities, has also proven to be cardioprotective against myocardial ischemia/reperfusion damage. However, the mechanism of this protective effect has not been clarified yet. The aim of this study was to determine whether this effect is due to protection against free radical induced changes. The experimental model in rabbits includes coronary artery ligation for 60 min followed by a reperfusion period of 45 min. In this model, free radical damage was estimated by different parameters of lipid peroxidation such as diene conjugation, carbonyl content, and thiobarbituric acid reactive substances, together with protein oxidation determinations. The results demonstrate that defibrotide prevents free radical induced changes after myocardial ischemia/reperfusion.
Keywords: antithrombotics; defibrotide, pharmacology; free radicals; myocardial ischemia/reperfusion, experimental; Prociclide(R); ACUTE MYOCARDIAL ISCHEMIA; LIPID-PEROXIDATION; PROSTACYCLIN; CAT; REPERFUSION; INFARCTION; LETHAL; TISSUE; HEART